Calculation of continuous beams taking into account the elastic compliance of supports - Nuguzhinov, Zh.S.; Akhmediev, S.K.; Zholmagambetov, S.R.; Khabidolda, O. (Bulletin of the Karaganda University. Mathematics Series, 2018)
This work considers multispan structures (beams, columns) supported on intermediate elastically compliant supports. The structures are also extensively used in high-rise construction. The research is carried out by an exact analytical force method, based on the equation of five moments. The basic resolving equations are given. The work of a two-span structure with elastically compliant supports is considered in detail. The chart of flexure, the bending moments and the lateral forces are obtained depending on the compliance coefficient α, which varies within the limits of 0, .., ∞. The analysis of the obtained results is carried out from the point of view of rational work of the operated structures.